المصلحة المرسلة وتطبيقاتها في المذهب الحنفي - حسين، فرحت (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
Maslahah mursalah (unrestricted public interest) is considered as one of the disputed evidences of Islamic jurisprudence and an important principle of ruling on new issues that are subject to ijtihad (juristic reasoning). The disagreement occured among the schools of Islamic law whether maslahah mursalah is considered as an evidence of Shariʻah or not. The disagreement also emerged among scholars whether Hanafi school considers maslahah mursalah as an evidence for deriving rulings of Shariʻah or not. However, the scope for further research and review on the issue is still there. At this very juncture, this research focuses on gathering opinions within Hanafi school regarding maslahah mursalah and studying them in order to understand the views and interpretations of Hanafi school for it. Besides, this study discusses the applications of maslahah mursalah in the field of business transaction from the perspective of Hanafi school. The researcher has used inductive, analytical and comparative approaches in order to achieve the objectives of this study. The major findings of the study include considering maslahah mursalah by the Hanafi school as an evidence for deriving ruling of the Shariʻah in the form of munasib mursal (unrestricted suitability) and istihsan (juristic preference). The differences between Hanafi school and other schools of jurisprudence regarding maslahah mursalah apprear while it is compared with istihsan. In this research, the application of maslahah mursalah from Hanafi perspective has been discussed in the field of istisnaʻ, mudarabah and daman. Thus, the study disapproves the assertion that Hanafi school does not consider maslahah mursalah as an evidence for deriving rulings of the Shariʻah.